PENGELOLAAN USAHA EKONOMI DESA/KELURAHAN SIMPAN-PINJAM (UED/K-SP) DI DESA GABUNG MAKMUR KECAMATAN KERINCI KANAN KABUPATEN SIAK - Syamsidar, Yusni; ", Ernawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Management Usaha Ekonomi Desa/Kelurahan Simpan-Pinjam (UED-SP) in Gabung Makmur village of Kerinci Kanan subdistrict Siak regency. Usaha Ekonomi Desa/Kelurahan Simpan-Pinjam (UED/K-SP) stipulated in Law Number 6 of 1998. Theoretical concepts used by George Terry (2003:3) which includes planning, organizing, directing, controlling. Main sources of this research is the Village Head of Gabung Makmur once authority UED/K-SP. This research is a qualitative descriptive with triangulation technique that means to reveal phenomena that occur in Management Usaha Ekonomi Desa/Kelurahan Simpan-Pinjam (UED/K-SP) as well as inhibiting factors. The resulte of this research showed Management Usaha Ekonomi Desa/Kelurahan Simpan-Pinjam (UED/K-SP) in Gabung Makmur village of Kerinci Kanan subdistrict Siak regency not optimal. This is because any some hindrance factors of UED/K-SP are the human resource is still low, utilizing karaker UED/K-SP, and financial resorces.Keywords : Management, UED/K-SP,SDM